Developments in intracerebral stem cell grafts. (April 2015) - Reyes, Stephanny; Tajiri, Naoki; Borlongan, Cesar V
Abstract : The field of stem cell therapy has emerged as a promising research area for brain repair. Optimizing the safety and efficacy of the therapy for clinical trials will require revisiting transplantation protocols. The cell delivery route stands as a key translational item that warrants careful consideration in facilitating the success of stem cell therapy in the clinic. Intracerebral administration, compared to peripheral route, requires an invasive procedure to directly implant stem cells into injured brain. Although invasive, intracerebral transplantation circumvents the prohibitive blood brain barrier in allowing grafted cells when delivered peripherally to penetrate the brain and reach the discreet damaged brain tissues. This review will highlight milestone discoveries in cell therapy for neurological disorders, with emphasis on intracerebral transplantation in relevant animal models and provide insights necessary to optimize the safety and efficacy of cell therapy for the treatment of Parkinson's disease, Huntington's disease, stroke and traumatic brain injury.